Utilization of Breadfruit (Artocarpus altilis) Skin Waste in Making Edible Film with the Addition of Glycerol and Chitosan Plasticizer Formulation - Ramadhan, Rahma Aula; Fizriani, Atia; Tubagus, Robi (FoodTech: Jurnal Teknologi Pangan, 2024)
The starch content in breadfruit skin has the potential as a constituent ingredient for making edible films. The addition of glycerol and chitosan plasticizers can produce good edible film characteristics. The aim of this research is to determine the effect, best treatment and application of shelf life on animal and vegetable products with the addition of glycerol and chitosan plasticizers on the chemical, physical and mechanical characteristics of breadfruit peel starch edible film. The method used was a non-factorial Completely Randomized Design (CRD) with 4 treatment levels and 3 replications using the experimental analysis method, then was used to determine shelf life. Based on the research results, the addition of various plasticizers, glycerol and chitosan, had a significant effect on the values of water content, ash content, thickness, tensile strength, elongation and water vapor transmission rate (WVTR). Treatment T1 has the best characteristics including, water content 13.05%, ash content 1.93%, thickness value 0.23 mm, water vapor transmission rate (WVTR) value 4.38 g/m2 hour, tensile strength value 12.57 Mpa, and elongation value 10.93%. The addition of various plasticizers, glycerol and chitosan, affects the shelf life of animal products in the form of pieces of chicken meat and vegetable products in the form of apple pieces packaged using edible film from breadfruit skin starch